2020
DOI: 10.1002/jmor.21238
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations for matrotrophy in the female reproductive system in the pseudoscorpion Chelifer cancroides (Chelicerata: Pseudoscorpiones, Cheliferidae)

Abstract: Pseudoscorpiones (pseudoscorpions, false scorpions) is an order of small terrestrial chelicerates. While most chelicerates are lecithotrophic, that is, embryos develop due to nutrients (mostly yolk) deposited in the oocyte cytoplasm, pseudoscorpions are matrotrophic, that is, embryos are nourished by the female. Pseudoscorpion oocytes contain only a small amount of yolk. The embryos develop within a brood sac carried on the abdominal site of the female and absorb nutrients by a pumping organ. It is believed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…In C. museorum (Figures 2a and 5a,c) and A. ferum (Figure 1b The structure of the female gonads in pseudoscorpions has been ana lyzed in a very few pseudoscorpion species including Garypus japonicus (Beier, 1952) (Garypidae) (Makioka, 1976(Makioka, , 1979, Pselaphochernes scorpioides (Hermann, 1804) (Chernetidae) (Weygoldt, 1969), and C. cancroides (Cheliferidae) (Badian & Ogorzałek, 1982;Jędrzejowska & Garbiec, 2020;Jędrzejowska et al, 2013). These studies unam biguously indicate that the mature ovaries in pseudoscorpions are unpaired tubular and grape shaped organs.…”
Section: Ovarian Wall and Stalk Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…In C. museorum (Figures 2a and 5a,c) and A. ferum (Figure 1b The structure of the female gonads in pseudoscorpions has been ana lyzed in a very few pseudoscorpion species including Garypus japonicus (Beier, 1952) (Garypidae) (Makioka, 1976(Makioka, , 1979, Pselaphochernes scorpioides (Hermann, 1804) (Chernetidae) (Weygoldt, 1969), and C. cancroides (Cheliferidae) (Badian & Ogorzałek, 1982;Jędrzejowska & Garbiec, 2020;Jędrzejowska et al, 2013). These studies unam biguously indicate that the mature ovaries in pseudoscorpions are unpaired tubular and grape shaped organs.…”
Section: Ovarian Wall and Stalk Cellsmentioning
confidence: 99%
“…During the first phase, termed oogenic, the oocytes grow and mature. In the second phase, named secretory, which starts after ovulation, the oocyte growth is ceased and the ovarian and oviductal epithelial cells secrete the nutritive fluid to nourish developing embryos (Jędrzejowska & Garbiec, 2020;Jędrzejowska et al, 2013;Makioka, 1976Makioka, , 1979.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to this hypertrophy, the postovulatory stalks become the most voluminous structures in the ovary. Our quite recent findings 32 revealed that in Chelifer two organs of the female reproductive system, that is, the ovary and the oviducts, are involved in the synthesis of the nutritive fluid. We also showed that during the secretory phase of the ovarian cycle, stalk cells together with epithelial wall cells of the ovary and oviducts undergo multistep hypertrophy and polyploidization and show structural similarities of secretory active cells 32 .…”
Section: Discussionmentioning
confidence: 98%
“…The embryonic development of C. cancroides is considered to show the most specialized traits 16 . Our previous investigations 32 revealed that in C. cancroides , secretion of the nutritive fluid is amplified due to the involvement in this process not only the epithelial cells of the ovary but also the oviducts. We also showed that the somatic cells that participate in the synthesis of nutritive fluid become highly enlarged as a result of multistep hypertrophy and polyploidization.…”
Section: Introductionmentioning
confidence: 98%